2021
DOI: 10.5114/ait.2021.108624
|View full text |Cite
|
Sign up to set email alerts
|

The value of sepsis biomarkers and their kinetics in the prognosis of septic shock due to bacterial infections

Abstract: Septic shock is a leading cause of mortality in critically ill patients, despite the use of new antibiotics and resuscitation therapies [1,2]. Given the significance of timely beginning of appropriate antibiotics to optimise septic shock outcomes [1, 2], clinicians must quickly achieve a diagnosis of infection. In fact, it is now accepted that starting an early effective antibiotic therapy in the course of an infection decreases morbidity and mortality in this specific condition [2,3]. Moreover, apart from

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The kinetics of CRP and PCT levels during the course of septic shock were investigated within a study by Bahloul et al including 60 patients, demonstrating a fall in CRP or PCT level was associated with improved prognosis [ 25 ]. On the other hand, CRP and PCT were inferior to interleukin-6 (IL-6) predicting treatment success in 328 patients with sepsis when re-assessed after 48–72 h [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The kinetics of CRP and PCT levels during the course of septic shock were investigated within a study by Bahloul et al including 60 patients, demonstrating a fall in CRP or PCT level was associated with improved prognosis [ 25 ]. On the other hand, CRP and PCT were inferior to interleukin-6 (IL-6) predicting treatment success in 328 patients with sepsis when re-assessed after 48–72 h [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of note, kinetics were different among survivors and non-survivors. CRP levels in survivors decreased after day 1 and remained high in non-survivors after an increase up to day 3 [38]. In line with this, Miki et al showed that CRP levels and peaks in patients admitted with sepsis depended on the individuals' outcomes.…”
Section: Discussionmentioning
confidence: 79%